Case report: Toceranib as adjuvant chemotherapy in a dog with incompletely resected combined hepatocellular-cholangiocarcinoma - Kim, Sang-Won; Choi, Ju-Won; Kim, Jeon-Mo; Yoon, Hun-Young; Bae, Kieun; Yoon, Kyong-Ah; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2023)
An 11-year-old intact female mixed breed dog was presented with abdominal distention and elevated hepatic enzyme levels. Computed tomography revealed a multicystic hepatic mass at the left medial lobe adjacent to the diaphragm and caudal vena cava. The mass was surgically removed with partial hepatectomy, but it could not be removed completely because of adhesion to the diaphragm. The tissue was submitted for histopathologic evaluation, and the patient was diagnosed with stage IIIA combined hepatocellular-cholangiocarcinoma (cHCC-CC). Considering the residual tumor tissue from incomplete surgical excision, adjuvant chemotherapy was recommended. Tumor tissue obtained from the patient was assessed using an anticancer drug response prediction test, and the results showed that toceranib phosphate was the most effective chemotherapeutic agent for this patient. Toceranib was initiated (3.1 mg/kg, PO, q48h), and routine adverse effect assessment, including systemic blood pressure measurement, complete blood count, serum biochemical evaluations, and urinalysis were performed at two-week intervals for the first two months and every two months thereafter. Radiography and ultrasonography were conducted at one-month intervals for the first two months and then every two months subsequently. Concurrent hyperadrenocorticism was managed with trilostane (1 to 5 mg/kg, PO, q12h). The patient showed no critical adverse effects of chemotherapy, obvious recurrence, or metastasis. The response to toceranib was assessed as a partial response, and the patient is still alive over 23 months after tumor excision. This is the first case report describing chemotherapy for a dog with cHCC-CC.